Executive compensation and bank risk in China - Huang, Qiubin (Economics and Business Letters, 2023)
Executive compensation is an important mechanism of corporate governance for banks, but its effect on bank risk remains inconclusive. Based on a sample of banks listed in China, we uncover a significantly positive relationship between executive compensation and bank risk during the 2007–2018 period. The finding is robust to model specifications, the risk measures used, and the way to calculate executive compensation.